A Curriculum for Enhancing Physician Teaching Skills: The Value of Physician-Educator Partnerships. (July 2021) - Hoffert, Mara M; Passalacqua, Karla D; Haftka-George, Alexis; Abreu Lanfranco, Odaliz; Martin, Robert A
Developing as a physician requires an enormous amount of complex training, and quality of instruction greatly affects training outcomes. But while physicians are expected to teach trainees within the clinic, they often do not receive formal training in effective instructional practices. Providing faculty development programs is one way that institutions can help physicians develop teaching skills, but these programs often are developed without the input of educational specialists and not based in educational theory. In this methodology paper, we describe a 5-module curriculum that was developed in a cross-disciplinary collaboration between instructional designers and physician faculty. By merging educational and medical expertise and using adult learning theory with the Charlotte-Danielson educational framework, an essentials for clinical teaching educational endorsement program (ECTEEP) was created as a feature of the institutional curriculum within a large, urban teaching hospital. Here we describe how the program was developed through a physician-educator partnership, outline the program's key content, and highlight essential aspects of successful implementation. The ECTEEP incorporates active learning approaches within an abbreviated format, distilling 5 critical aspects of effective teaching that are relevant to the clinical environment: cultural humility and safe learning environments, instruction practices for engaging learners, instruction and assessment strategies, receiving and giving feedback, and mentorship and coaching. A central feature of the program is that facilitators actively model the teaching behaviors they are conveying, which underscores the critical importance of facilitator preparation and skill. Our curriculum is offered here as a basic template for institutions that may want to establish a program for enhancing physician teaching skill.